Vascular endothelial cell mechanosensing: New insights gained from biomimetic microfluidic models. (November 2017) - Gray, Kelsey M.; Stroka, Kimberly M.
Graphical abstract: Abstract: In vivo, cells of the vascular system are subjected to various mechanical stimuli and have demonstrated the ability to adapt their behavior via mechanotransduction. Recent advances in microfluidic and "on-chip" techniques have provided the technology to study these alterations in cell behavior. Contrary to traditional in vitro assays such as transwell plates and parallel plate flow chambers, these microfluidic devices (MFDs) provide the opportunity to integrate multiple mechanical cues (e.g. shear stress, confinement, substrate stiffness, vessel geometry and topography) with in situ quantification capabilities. As such, MFDs can be used to recapitulate the in vivo mechanical setting and systematically vary microenvironmental conditions for improved mechanobiological studies of the endothelium. Additionally, adequate modelling provides for enhanced understanding of disease progression, design of cell separation and drug delivery systems, and the development of biomaterials for tissue engineering applications. Here, we will discuss the advances in knowledge about endothelial cell mechanosensing resulting from the design and application of biomimetic on-chip and microfluidic platforms.